High‐Resolution 3D Printed Photonic Waveguide Devices. Issue 18 (12th July 2020) - Gao, Hongwei; Chen, George F. R.; Xing, Peng; Choi, Ju Won; Low, Hong Yee; Tan, Dawn T. H.
Abstract: Photonic building blocks fabricated using two‐photon polymerization laser lithography are reported. 3D polymer structures are fabricated using a direct laser writing process with nonlinear two‐photon absorption in photosensitive material. The 3D photonic structures include 3D photonic waveguides, Bragg gratings, and resonators. In particular, high‐quality spiral and air‐bridge waveguides providing 3D light guiding beyond a single plane are demonstrated. Sub‐micrometer features as well as unique coupling interfaces with 1.6 dB coupling losses and large 3 dB bandwidth are also demonstrated. Experimental characterization reveals the good transmission performance of the fabricated photonic devices. In addition, the waveguides are demonstrated to support 30 Gb s −1 NRZ (nonreturn to zero) and 56 Gb s −1 PAM4 (pulse amplitude modulation 4) high‐speed data. Small power penalties of 0.7 dB for NRZ (BER = 10 −12 ) and 1.5 dB for PAM4 (BER = 10 −6 ) are obtained. Abstract : 3D photonic devices fabricated using two‐photon polymerization laser lithography, including high‐resolution photonic waveguides, Bragg gratings and resonators are demonstrated. High‐quality spiral and air‐bridge waveguides providing 3D light guiding, unique couplers with 1.6 dB coupling loss and large 3 dB bandwidth are also demonstrated. The waveguides support 30 Gb s −1 NRZ (nonreturn to zero) and 56 Gb s −1 PAM4 (pulse amplitude modulation 4) high‐speed data.